The vagrant mood - Maugham, W. Somerset (London : Vintage Books, 2011)
The Vagrant Mood is a brilliantly varied and colourful collection of essays. From Kant to Raymond Chandler; from the legend of Zurbaran to the art of the detective story; from Burke to Augustus Hare, Somerset Maugham brings his inimitable mastery of the incisive character sketch to the genre of literary criticism
Keywords: Mandarin non-fiction.